Fluid Invasion Dynamics in Porous Media With Complex Wettability and Connectivity. Issue 22 (11th November 2021) - Mascini, Arjen; Boone, Marijn; Van Offenwert, Stefanie; Wang, Shan; Cnudde, Veerle; Bultreys, Tom
Abstract: Multiphase flow is important for many natural and engineered processes in subsurface geoscience. Pore‐scale multiphase flow dynamics are commonly characterized by an average balance of driving forces. However, significant local variability in this balance may exist inside natural, heterogeneous porous materials, such as rocks and soils. Here, we investigate multiphase flow in heterogeneous rocks with different wetting properties using fast laboratory‐based 4D X‐ray imaging. The mixed‐wet dynamics were characterized by displacement rates that differed over orders of magnitude between directly neighboring pores. While conventional understanding predicted strongly capillary‐dominated conditions, our analysis suggests that viscous forces played a key role in these dynamics, facilitated by a complex interplay between the mixed‐wettability and the pore structure. These dynamics highlight the need for further studies on the fundamental controls on multiphase flow in geomaterials, which is crucial to design, for example, groundwater remediation and subsurface CO2 storage operations. Plain Language Summary: The flow of multiple fluids through a porous material plays an important role in many industrial and natural processes such as rain infiltrating a dry soil or CO2 storage in the subsurface. At the pore‐scale, these flows are governed by forces which depend on the pore‐geometry and the relative affinities of the fluids with the solid (i.e., wettability). The rates at which fluids flow in geological reservoirs is in most cases considered to be very slow (in the order of tens of meters per year). At these slow flow rates, fluid displacements are thought to be controlled by capillary forces. However, much of our current understanding of multiphase flow stems from artificial samples with simplified geometries, while most natural geomaterials tend to be far more complex in terms of pore structure and wettability. We show that heterogeneous pore structures and wetting properties can lead to different mechanisms of fluid displacement compared to those observed in model materials due to local variations in the viscous‐capillary force balance. This implies that models commonly used to predict subsurface flow process such as geological CO2 storage that assume capillary forces to dominate may not adequately capture the dynamics at the pore‐scale. Key Points: The pore‐scale dynamics of multiphase flow in heterogeneous rocks were investigated using fast laboratory‐based 4D X‐ray microtomography We describe a pore‐scale displacement mechanism with displacement rates orders of magnitude slower than those in neighboring pores We demonstrate that viscous forces could play a significant role even at very low global capillary numbers under mixed‐wet conditions